Self-expanding Y stents in the treatment of central airway stenosis: a retrospective analysis - Gompelmann, Daniela; Eberhardt, Ralf; Schuhmann, Maren; Heußel, Claus Peter; Herth, Felix (Therapeutic advances in respiratory disease, 2013)
Background:Central airway obstruction (CAO) is a life-threatening situation. Stent insertion re-establishes patency of the central airways. Self-expanding metallic Y stents have been available since 2005, widening the spectrum of interventional bronchoscopic techniques.Methods:Retrospective analysis of all patients treated for CAO with a self-expanding metallic Y stent at the Thoraxklinik Heidelberg between May 2005 and January 2009.Results:A total of 43 patients aged 26?81 had a metallic Y stent inserted endoscopically for the treatment of CAO; 39 of these patients (90.7%) had CAO due to malignant disease, four patients (9.3%) due to benign disease. In all 43 patients, the Y stent was deployed without any complications. A longitudinal follow up was possible in 32 of the 43 patients. The stents remained in situ for an average of 107.1 days (range 1?640 days). In 29 patients with malignant CAO the stenosis was successfully overcome with a Y stent; 11 of these patients died within 6 weeks following stent insertion. On follow up the remaining 18 patients showed immediate improvement of dyspnoea. Eight out of the 18 patients (44.4%) tolerated the stent without problems, two (11.1%) required further stenting, six (33.3%) had complications such as increased secretions, cough, dyspnoea or granulation tissue formation. The stent was removed in one patient (5.6%) due to increased secretions, and in another (5.6%) as the stent was no longer required due to successful tumour-specific therapy.Conclusion:Placement of Y stents in symptomatic CAO allows for quick relief of symptoms. Severe complications are rare. Stent removal is possible after successful treatment of the primary tumour. However, the prognostic indicator for survival is the underlying malignancy.
Gesehen am 18.02.2020